(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Patient safety is an emerging field in healthcare that has indirectly or directly affected all stakeholders of healthcare delivery system in the last decade. World Health Organization guidelines for adverse event reporting and learning systems, 2005 describes adverse events as “an injury related to medical management in contrast to complications of disease.” These adverse events can be preventable or nonpreventable. Inpatient falls presents a serious challenge to the safety and quality of patients in hospitals. Falls are not harmless, they delays in functional recovery and prolonged hospitalization that can cause patients to suffer. The study was conducted to estimate the incidence and major reasons for falls. Methods: Retrospectively, case records from January 2016 to September 2018 of all the inpatients were researched for patient fall incidents, reported to the committee. The committee findings noted and the costs were estimated in terms of cost to the patients, and costs to the hospital. Results: 118 incidents of patient fall happened in study period. 3(2.6%) of them experienced two or more falls during stay, 115 (97.4%) fell once. 5 patients were morbidly obese. Costs to the hospital on each patient was Rs. 5412/-, not levied on patients. Conclusion: The number of fall incidents and falls reporting system have been improved by early detection of reasons by conducting root cause analysis.